Constrained harmonization algorithm for pooling multi‐site datasets. (31st December 2021) - Lokhande, Vishnu Suresh; Mishra, Akshay; Diers, Kersten; Düzel, Emrah; Reuter, Martin; Bendlin, Barbara B; Singh, Vikas
Abstract: Background: Pooling datasets from multiple studies can significantly improve statistical power: larger sample sizes can enable the identification of otherwise weak disease‐specific patterns. When modern learning methods are utilized (e.g., for predicting progression to dementia), differences in data acquisition‐methods / scanner‐protocols can enable the model to "cheat", i.e. utilizes site‐specific artifacts rather than disease‐specific features. In this study, we develop a method to harmonize the performance of DNN classifiers across scanners/sites, via so‐called fairness constraints, thereby encouraging consistent behavior while controlling for site‐specific nuisance variables. Method: We conducted two studies: (a) to demonstrate feasibility of pooling across sites (Site‐Pooling) and (b) to pool data across scanners (Scanner‐Pooling). For Site‐Pooling, our analysis included summaries from Freesurfer processed T1‐weighted images of the Wisconsin Alzheimer's Disease Research Center (ADRC) and German Center for Neurodegenerative Diseases (DZNE). The Freesurfer summaries were used to train a two layer neural network classifier and five‐fold cross‐validation performance was assessed. For Scanner‐Pooling experiments, Freesurfer processed MR images from the Alzheimer's Disease Neuroimaging Initiative (ADNI) were used to train a deep 3D convolutional network. Performance average on a held‐out test dataset was evaluated. In both cases, a constraint to equalize the performance of the trained classifier across the domains (sites/scanners) was incorporated during training. Result: Table 1 shows the results of AD/MCI classification for site‐pooling analysis. Our proposed method is compared against a naive pooling approach which does not incorporate the "harmonization constraint". As shown, the proposed method improves the "difference of errors" measure by 8% / 7% and with only a small drop in overall error rates. Figure 1 illustrates the results from our scanner‐pooling analysis. The performance across the three scanners, GE, Siemens and Philips, is evaluated pair‐wise. A consistent improvement in harmonization is observed and only ∼2% drop in overall error rate is seen. Conclusion: We provide a harmonization constraint based algorithm to mitigate site specific differences when performing analysis of pooled brain imaging datasets in AD studies. In contrast to a method which modifies the data, we achieve harmonization by constraining the classifier to perform similarly across sites/groups/scanners, improving reproducibility.